(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
The article deals with the linguistic features expressing Ukrainian mentality in the novel «Khiba revut voly, yak yasla povni» by Panas Myrnyi and Ivan Bilyk. The features which are typical for Ukrainian nation are pointed out. Attention is focused on lexical-semantic means of thinking and world outlook of Ukrainians in the text of the novel.